2005
DOI: 10.1348/135910705x25985
|View full text |Cite
|
Sign up to set email alerts
|

Emergency contraception use and non‐use in young women: The application of a contextual and dynamic model

Abstract: There have been many approaches to understanding contraception use including social cognition models which have been criticised for their individualistic approach and their static nature. The present quantitative study developed and refined a contextual and dynamic model of contraception use that was derived using qualitative research. This model conceptualizes the predictors of contraception use in terms of the meaning and importance of a range of social goals, perceptions of vulnerability, and constraints on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Reproductive decision making includes a myriad of emotions along with cognitive processes that are impacted by many contextual factors (Lerner, 2002). One of these factors is the role that male partners play (Free & Ogden, 2005). To date, only limited research has explored this relationship.…”
Section: Complexities Of Contraceptive Decision Makingmentioning
confidence: 99%
“…Reproductive decision making includes a myriad of emotions along with cognitive processes that are impacted by many contextual factors (Lerner, 2002). One of these factors is the role that male partners play (Free & Ogden, 2005). To date, only limited research has explored this relationship.…”
Section: Complexities Of Contraceptive Decision Makingmentioning
confidence: 99%
“…This finding is extremely relevant, since it indicates that the EC is underutilized among a highly educated population in a context of high use of contraceptive methods. Lack recognition of pregnancy risk are shown to deter women from using EC despite having had unprotected intercourse (Raine 2005;Moreau 2005;Sørensen, Pedersen, Nyrnberg, 2000;Free, Lee, Ogden, 2002;Free, Ogden, 2005;Goulard et al, 2006;Nappi et al, 2014;Santos et al, 2014). In the same line, we also found that 40% of women in our study reported having had unprotected sexual intercourse within 12-months prior to the survey and had not used EC to reduce the risk of pregnancy.…”
Section: Discussionsupporting
confidence: 77%
“…A study of Latina women in the United States showed that positive attitudes toward EC were linked with increasing knowledge of its proper use and of its mechanism of action. Moral or religious concerns also affect women's attitudes toward EC, and are commonly cited as reasons why women would not use it 32,34,35 …”
Section: Women's Knowledge Attitudes and Practicesmentioning
confidence: 99%
“…Moral or religious concerns also affect women's attitudes toward EC, and are commonly cited as reasons why women would not use it. 32,34,35 Statistics on EC use are difficult to compare, as they are gathered from different populations with different demographics, making it almost impossible to determine the true trend of EC use. A study of college students conducted in 2003 reported a 13.7% use rate.…”
Section: Women's Knowledge Attitudes and Practicesmentioning
confidence: 99%